Rapid automatized naming (RAN) and reading fluency implications for understanding and treatment of reading disabilities.[article]. - Norton, Elizabeth S
Fluent reading depends on a complex set of cognitive processes that must work together in perfect concert. Rapid automatized naming (RAN) tasks provide insight into this system, acting as a microcosm of the processes involved in reading. In this review, we examine both RAN and reading fluency and how each has shaped our understanding of reading disabilities. We explore the research that led to our current understanding of the relationships between RAN and reading and what makes RAN unique as a cognitive measure. We explore how how the automaticity that supports RAN affects reading across development, reading abilities, and languages, and the biological bases of these processes. Finally, we bring these converging areas of knowledge together by examining what the collective studies of RAN and reading fluency contribute to our goals of creating optimal assessments and interventions that help every child become a fluent, comprehending reader. - (from the authors)